Light controlled self‐escape capability of non‐cationic carbon nitride‐based nanosheets in lysosomes for hepatocellular carcinoma targeting stimulus‐responsive gene delivery - Ming‐Xuan Liu; Li Xu; Jia‐Yi Jiang; Hai‐Chen Dong; Peng‐Fei Zhu; Lei Cao; Jing Chen; Xiao‐Ling Zhang (Wiley, 2023)
Abstract High positive charge‐induced toxicity, easy lysosomal degradation of nucleic acid drugs, and poor lesion sites targeting are major problems faced in the development of gene carriers. Herein, we proposed the concept of self‐escape non‐cationic gene carriers for targeted delivery and treatment of photocontrolled hepatocellular carcinoma (HCC) with sufficient lysosome escape and multiple response capacities. Functional DNA was bound to the surface of biotin‐PEG2000‐modified graphitic carbon nitride (Bio‐PEG‐CN) nanosheets to form non‐cationic nanocomplexes Bio‐PEG‐CN/DNA. These nanocomposites could actively target HCC tissue. Once these nanocomplexes were taken up by tumor cells, the accumulated reactive oxygen species (ROS) generated by Bio‐PEG‐CN under LED irradiation would disrupt the lysosome structure, thereby facilitating nanocomposites escape. Due to the acidic microenvironment and lipase in the HCC tissue, the reversible release of DNA could be promoted to complete the transfection process. Meanwhile, the fluorescence signal of Bio‐PEG‐CN could be monitored in real time by fluorescence imaging technology to investigate the transfection process and mechanism. In vitro and in vivo results further demonstrated that these nanocomplexes could remarkably upregulate the expression of tumor suppressor protein P53, increased tumor sensitivity to ROS generated by nanocarriers, and realized effective gene therapy for HCC via loading P53 gene.